Highly Stable, Flexible, Anticorrosive Coating of Metalized Nonwoven Textiles for Durable EMI Shielding and Thermal Properties - Khan, Muhammad Zaman; Taghavian, Hadi; Zhang, Xiuling; Militky, Jiri; Ali, Azam; Wiener, Jakub; Tunáková, Veronika; Venkataraman, Mohanapriya; Dvorak, Lukas (ACS omega, 2025)
In the present research, an advanced silane-bonded polydopamine (PDA) coating through a simple, low-cost, and highly effective technique was employed to enhance the stability of copper-coated electromagnetic shielding fabrics. Coating the metalized nonwoven PET fabric with PDA can protect it from oxidation, mechanical forces, and extreme chemical conditions such as acid and alkali corrosion. The coated nonwoven fabric retained its excellent electromagnetic shielding effect even after machine- and handwashing cycles, showing average shielding effectiveness (SE) values above 41 dB for PDA@MEFTEX and Si-QAC/PDA@MEFTEX samples, and the average SE remained consistently above 39 dB under acidic and alkaline conditions. The PDA-coated MEFTEX did not significantly increase the surface and volume resistivities and exhibited excellent thermal insulation properties. In addition, silane-bonded PDA coating increased the softness, acted as a barrier, and provided a perfect interface that inhibits the penetration of corrosive ions from the surroundings. This outcome further highlights the promising impact of the novel coating, serving as protective coverage for metalized nonwoven fabric and providing good physical and thermal properties. This method can effectively protect electromagnetic shielding cloth, prolong the use time of shielding material, and expand its scope of application.